Estrategias didácticas que promueven la participación activa de los estudiantes en el PEA de Biología año lectivo 2023-2024. - Chamba Iñiguez, Sonia Fiorella (2024)
The didactic strategies implemented in the development of the teaching-learning process of Biology are important, since they promote the active participation of students and improve their academic performance. The objective of this research was: "To strengthen the academic performance of students through the application of didactic strategies that allow their active participation in the development of the teaching-learning process of Biology in the second year of UGB, of Lauro Damerval Ayora Educative Unit, academic year 2023 - 2024". The method used was inductive, through direct observation, the lack of application of didactic strategies in the development of the classroom process was identified, which limits the active participation of students, through bibliographic research the intervention proposal was elaborated to improve the identified reality. The approach was qualitative, it allowed determining the qualities and relevant characteristics in the development of the classroom process. According to the nature of the information, it corresponds to Participative Action Research, since through the development of the intervention proposal we interacted with the students, to achieve the improvement of their academic performance. According to the temporality, it is transversal, since it was developed in a relatively short time. In addition, in the results obtained through the evaluation and research instruments applied, it is reflected that the implementation of didactic strategies such as: problem-based learning, information management, content fair, inverted classroom, learning by discovery and explanatory-dialogue, promotes the active participation of students in the teaching-learning process of Biology, which improves their academic performance, demonstrated in the contrast of grades before and after the intervention. Finally, it is concluded that by applying didactic strategies in the development of the teaching-learning process of Biology, the active participation of the students is promoted and consequently their academic performance is strengthened. Key words: academic performance, constructivism, meaningful learning, classroom process.